Robin Blackburn (ed.), Explosion in a Subcontinent; India, Pakistan, Bangladesh and Ceylon, Penguin Books and New Left Review, Pelikan Books, London, 1975, 378 pp. - G. M., J. P. (El Colegio de México, 1976)
-